Determinants of foreign direct investment in Sub-Saharan African countries - AMBAYE, Adugna Ameha (KDI School, 2016)
The main objective of this thesis is to examine factors that determine FDI inflows to go or not to go in to Sub-Saharan Africa countries. Forty four Sub-Saharan African countries were sampled over the period of 1990 up to 2013. A balanced panel data analysis employed and estimated via pool ordinary least square (OLS), random effects (RE) and Fixed effect (FE). Among the three model based on husman test and an F-test fixed effect (FE) was found the appropriate model. To determine factors that affect FDI inflow, I used Trade openness, Natural Resource, Inflation, FDI lag, Return on investment, Corruption, Urban Population, Infrastructure, and Contract Enforcement as explanatory variables. The finding show that ;Trade openness, Natural Resources, FDI_1, Return on Investment (ROI), Urban Population, and Corruption are the most important determinants of FDI inflow at less than 5% level of significance . Whereas Infrastructure and Contract Enforcement, not statistically significance in determine FDI, but their sign of coefficient is as anticipated.
Thesis(Master) --KDI School:Master of Development Policy,2016